Impact assessment of IFPRI's Agricultural Science and Technology Indicators (ASTI) Project - Norton, George W. (International Food Policy Research Institute, 2010)
Well-funded and well-staffed agricultural research systems with efficient allocation of research resources are important for improving agricultural productivity and for meeting other agricultural development goals. Assessing research system funding adequacy and staffing, as compared to alternative investments, and allocating research resources within systems require data on agricultural research investments. The Agricultural Science and Technology Indicators (ASTI) initiative at IFPRI is the most comprehensive source of agricultural research statistics for low- and middle-income countries. Since 2001, building on an earlier International Service for National Agricultural Research (ISNAR) effort, ASTI has developed a network of institutional collaborators at national and regional levels who assist in implementing surveys to collect agricultural research investment data in Africa, Asia, the Middle East, and Latin America. ASTI compiles, processes, and publicizes the data at national, regional, and global levels. It has published a broad set of country briefs, notes, and regional synthesis reports that have been cited in national and international policy documents.